2017
DOI: 10.5005/jp-journals-10066-0045
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Ultrasound-guided Suprascapular Nerve Block and Extracorporeal Shock Wave Therapy in Reduction of Pain and Functional Disability in Adhesive Capsulitis of Shoulder: A Randomized Controlled Study

Abstract: Objective: To compare the effectiveness of ultrasound-guided suprascapular nerve block (SSNB) and extracorporeal shockwave therapy (ESWT) in the management of adhesive capsulitis of the shoulder. Study design: Randomized controlled trial.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 19 publications
(23 reference statements)
0
1
0
Order By: Relevance
“…Many studies have reported short term benefits in pain relief and range of movement after SSNB. 5,10,12,18 But only one study has raised question about the long-term benefits of SSNB in terms of pain relief, active and passive shoulder range of motion, disability, and overall quality of life; citing no improvement in assessment scores from 3 to 12 months post intervention. 19 This point of conflict could be due to natural healing process, heterogeneity of study population, variability of assessment tools, and adjunctive therapies.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have reported short term benefits in pain relief and range of movement after SSNB. 5,10,12,18 But only one study has raised question about the long-term benefits of SSNB in terms of pain relief, active and passive shoulder range of motion, disability, and overall quality of life; citing no improvement in assessment scores from 3 to 12 months post intervention. 19 This point of conflict could be due to natural healing process, heterogeneity of study population, variability of assessment tools, and adjunctive therapies.…”
Section: Discussionmentioning
confidence: 99%